If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 160 + x = 60 Solving 160 + x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-160' to each side of the equation. 160 + -160 + x = 60 + -160 Combine like terms: 160 + -160 = 0 0 + x = 60 + -160 x = 60 + -160 Combine like terms: 60 + -160 = -100 x = -100 Simplifying x = -100
| 7x+3(x+2)=-24 | | 8x+4y=254 | | 10x^2-(5/6)x-25=0 | | 9x+7=8x-8 | | 6x+27=11x+7 | | 2x^2-7x-39=0 | | 7x+11=11x+7 | | 7x+11=6x+27 | | 50=7x-6 | | 2(2-4x)=10-x | | 9-(2x+5)=3(2x+4) | | 8=x-13 | | x^3+14x=123 | | (4*4)+(r*r)=(r*r)*2*2 | | (4u^2)3/2 | | 3x+12=6x+3 | | m/-3+8=5 | | -24+3r=9 | | -24+3r=99 | | f=(1.8xC)+32 | | 75-7x=20x+18 | | 3+2c=12 | | 2x+12=-12-12x | | 4x-5+3x=8+6x | | 15x-5(x-1)=120+5x | | -41/3z+2 | | (2x+4)(8x-2)=0 | | 5=2w-9 | | (3+2*i*z)/(z+6*i)=z | | 150=2w+90 | | 5u+15=65 | | 5w+3=2w-6 |